2018
DOI: 10.1186/s11671-018-2604-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc Acetate Concentration on Optimization of Photocatalytic Activity of p-Co3O4/n-ZnO Heterostructures

Abstract: In this work, p-Co3O4/n-ZnO heterostructures were fabricated on Ni substrate by hydrothermal-decomposition method using cobaltous nitrate hexahydrate (Co(NO3)2·6H2O) and zinc acetate dihydrate (Zn(CH3COO)2·2H2O) as precursors with zinc acetate concentration varying from 5.0 to 55.0 mM. Structure and morphology of the developed samples were characterized by X-ray diffraction (XRD), Raman spectroscopy, and scanning electron microscopy (SEM). Effect of zinc acetate concentration on the photocatalytic activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…32 Five peaks at 191.6 cm −1 , 464.4 cm −1 , 503.3 cm −1 , 604.8 cm −1 and 665.1 cm −1 are observed and identified as Raman-active modes of Co 3 O 4 . [33][34][35][36][37] This gives the evidence of the successful synthesis of Co 3 O 4 /GO composites. The characteristic peaks of GO can't be detected clearly in the Raman spectra of Co 3 O 4 /GO-5 composite, this may be caused by the small content ratio of GO.…”
Section: Resultsmentioning
confidence: 70%
“…32 Five peaks at 191.6 cm −1 , 464.4 cm −1 , 503.3 cm −1 , 604.8 cm −1 and 665.1 cm −1 are observed and identified as Raman-active modes of Co 3 O 4 . [33][34][35][36][37] This gives the evidence of the successful synthesis of Co 3 O 4 /GO composites. The characteristic peaks of GO can't be detected clearly in the Raman spectra of Co 3 O 4 /GO-5 composite, this may be caused by the small content ratio of GO.…”
Section: Resultsmentioning
confidence: 70%
“…Fabrication of 2D p-n heterojunctions of semiconductor oxides is one of the key directions of future development of nanostructures with unique distinguishable properties, as they are able to combine various outstanding features of both semiconductors at the nanoscale [14]. However, it is extremely challenging to fabricate them defects-free over the wafer area, particularly when the thickness of each oxide is only few nanometers [2].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, fabrication of efficient n-p heterojunctions has been proposed and attempted with the different levels of success during the last few years [4, 17, 2022]. Specifically, it was found that the fabricated n-p heterojunctions could sufficiently reduce the recombination rate of the photo-generated electron/hole pairs with the following enhancement of the overall photocatalytic activity [1, 23, 24]. Thus, the combination of p- and n- type semiconductor oxides has paved the way for the further development of n-p heterojunctions and optimization of their photocatalytic capabilities [25].…”
Section: Introductionmentioning
confidence: 99%
“…Under UV irradiation, the excited electrons in the CB of CuO can easily move to the CB of ZnO, whereas the holes in the VB of ZnO can migrate into the VB of CuO. Thus, the number of photoexcited holes in the CuO-ZnO heterostructure increases [49], which leads to the higher photocatalytic activity.…”
Section: Photocatalytic Degradation Experimentsmentioning
confidence: 99%